Edukasi Pencegahan Penularan Covid-19 pada Ibu Hamil di Kota Jambi - Safitri Safitri (Jurnal Abdimas Kesehatan (JAK), 2021)
Covid-19 is a disease caused by a new type of coronavirus, namely Sars-CoV-2, which was first reported in Wuhan China on December 31, 2019. Pregnant women are one of the vulnerable groups at risk of being infected with Covid-19 due to physiological changes that have resulted in a decrease partial immunity. Initial studies found that many pregnant women do not implement health protocols in their daily lives and lack knowledge of Covid-19 and than prevention. One of the efforts that can be made in providing knowledge related to prevention measures for Covid-19 transmission is through online educational videos. This community service activity was implemented on pregnant women in Jambi City, with a total sample of 20 pregnant women. The expected outcome target is to increase knowledge between before and after being given an online educational video. The method used is online health education using educational video media that can be accessed via YouTube. Knowledge of pregnant women was assessed through the results of questionnaire via google form. Monitoring and evaluation of activities using the One Group Pretest and Post-test Design approaches. The result of service has increased knowledge after being given online educational videos as an effort to prevent Covid-19 transmission